Comparison between success rates for smokers re‐treated by a smokers' clinic and success rates for smokers treated for the first time. - Stepankova, Lenka; Kralikova, Eva; Zvolska, Kamila; Pankova, Alexandra; Adamcekova, Zuzana; Kuhn, Matyas; Noland, Derek (Addiction, 2021)
Aims: To compare success rates and characteristics of smokers treated a second time by a smokers' clinic with success rates of their first treatment. Design Retrospective cohort study. Setting: Tobacco Dependence Treatment clinic in Prague, Czech Republic, between 2005 and 2017. Participants: A total of 5225 smokers treated either once (n = 5006, single treatment sample, SS) or also second time (n = 219, re‐treated sample, RS), on average 4.47 years after the first visit. Intervention: Smokers received intensive treatment of tobacco dependence with pharmacotherapy options. Outcomes were evaluated after 1 year. In case of failure or relapse, participants could undergo re‐treatment in the same setting at least 1 year after the start of the first treatment. Measurements Twelve‐month self‐reported continuous abstinence; CO‐validated (≤ 6 parts per million); number of visits; type of pharmacotherapy; mental health history; Fagerström Test for Cigarette Dependence; time between first and second treatment. Results: The abstinence rate in the SS was 34.8% [95% confidence interval (CI) = 33.4%, 36.1%] and in the RS was 37% (95% CI = 30.6%, 43.8%) and 39.7% (95% CI = 33.2%, 45.5%) for their first and second treatments, respectively. The samples were comparable on smoking and socio‐demographic characteristics and pharmacotherapy used, but the RS in the second treatment had a higher prevalence of diagnosed mental health disorder at 39.3% (95% CI = 32.8%; 46.1%) compared with 23.7% (95% CI = 22.5%; 24.9%) in the SS. Participants who initiated their second quit attempt 1 to 2 years after the first one were less successful than those who initiated their second quit attempt later (25 versus 43%; P < 0.05). The results of the first treatment cycle were not found to be a reliable predictor for outcomes of the second cycle of treatment in univariate or multivariate logistic regression (odds ratio = 1.35, 95% CI = 0.70–2.63, P = 0.373). Conclusion: In Prague, Czech Republic, smokers re‐attending stop‐smoking treatment more than 2 years after their previous quit attempt appear to achieve similar success rates to those being treated for the first time.